Eksplorasi peringatan kesehatan bergambar pada kemasan rokok - Fahmi Baiquni; Fatwa Sari Tetra Dewi; Rendra Widyatama (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Exploration of pictorial health warnings in cigarette packagesPurposeThis study conducted to examine effectiveness of pictorial health warnings in cigarette packages to reduce smoking intention.MethodA population-based, qualitative study, were used in this study. 20 partisipants were observed and indept-interviewed. ResultsThreats after seeing a picture warnings on cigarette packs is the perception of the dangers of images and feelings of fear, disgust, pity, worry, mediocre. Efficacy after seeing a picture warnings on cigarette packs is the belief of the image and the impact on individuals after viewing images.ConclusionThreat of pictorial warnings are not only affected by the warning image itself but also the experience of the viewer and aspects of the warning image such as color, clarity of image, and message content.